Compatibility study of paracetamol, chlorpheniramine maleate and phenylephrine hydrochloride in physical mixtures - G.G.G. de Oliveira; A. Feitosa; K. Loureiro; A.R. Fernandes; E.B. Souto; P. Severino (Elsevier, 2017)
Paracetamol (PAR), phenylephrine hydrochloride (PHE) and chlorpheniramine maleate (CPM) are commonly used in clinical practice as antipyretic and analgesic drugs to ameliorate pain and fever in cold and flu conditions. The present work describes the use of thermal analysis for the characterization of the physicochemical compatibility between drugs and excipients during the development of solid dosage forms. Thermogravimetric analysis (TGA) and Differential Scanning Calorimetry (DSC) were used to study the thermal stability of the drug and of the physical mixture (drug/excipients) in solid binary mixtures (1:1). DSC thermograms demonstrated reproducible melting event of the prepared physical mixture. Starch, mannitol, lactose and magnesium stearate influence thermal parameters. Information recorded from the derivative thermogravimetric (DTG) and TGA curves demonstrated the decomposition of drugs in well-defined thermal events, translating the suitability of these techniques for the characterization of the drug/excipients interactions.